Anxiety spectrum disorders are common in patients with orthostatic tremor. (2019) - Bhatti, D.E.; Thompson, R.J.; Malgireddy, K.; Syed, N.M.; Bayer, B.; Bessette, D.; Fleisher, M.H.; Murman, D.L.; Torres-Russotto, D.
Abstract: Background: Orthostatic Tremor (OT) is a rare movement disorder characterized by a sensation of unsteadiness while standing and associated with high frequency tremors. Patients with OT commonly report a fear of falling and significant limitations in everyday activities. The prevalence of psychiatric comorbidities in OT patients has not been well-studied. Methods: Subjects were evaluated by trained psychiatry researchers using the Mini International Neuropsychiatric Interview (M.I.N.I.). The M.I.N.I is a validated screening tool for psychiatric disorders. A standardized history covering previous psychiatric symptoms and illnesses was also obtained. Results: 29 OT subjects were evaluated. The mean age was 67.7 years with female preponderance (89.3%). The average disease symptom duration was 18.2 years. 58.6% of the subjects had seen a mental health professional during the course of their OT illness. 24.1% of the subjects had a past history of depression, and 10.3% reported a family history of any psychiatric condition. 37.9% of the subjects screened positive for agoraphobia. Two of 29 subjects (6.9%) were classified as having a current major depressive episode and one subject (3.4%) was at risk for suicide. Conclusions: Psychiatric comorbidities are highly prevalent in OT patients, especially anxiety-spectrum disorders. Further studies are needed to understand if psychiatric disorders appear as a secondary response to the patient's symptoms, or are a primary non-motor manifestation of OT.